ANALISIS PENGARUH KONSUMSI ENERGI DAN EMISI CO2 TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA PERIODE 1981-2014 - Zuldareva, Fikri (Jurnal Ilmiah Mahasiswa FEB, 2017)
Economic activity is currently not avoid the use of natural resources, especially natural resources to produce energy. Consumption or energy consumption is a means to drive the industrialization of the economy as well as a means of capital accumulation of the good development of complementary or substitution to generate outputs in the economy. But in its development of energy use should be accompanied by policies that support the use of energy that can be used as needed. With that in discussing the condition Indonesian Energy journal covering production, consumption, and energy reserves of Indonesia then the impact of the energy use. of it, then the purpose of this study was to analyze the effect of Gross Fixed Capital Formation, Labor, Energy Consumption and CO2 Emissions on Economic Growth in Indonesia in 1981-2014. The approach used is a quantitative approach with descriptive methods. The type of data in this research is data Time Series of the Year 1981-2014. The analysis tool used is multiple linear regression. The results obtained are the Gross Fixed Capital Formation, Energy Consumption and CO2 Emissions positive and significant impact on Indonesia's Economic Growth 1981-2014. While Labor significant negative effect on economic growth in Indonesia in 1981-2014.Keywords: Economic Growth, Gross Fixed Capital Formation, Labor, Energy Consumption, CO2 Emissions